2012
DOI: 10.1186/1471-230x-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracellular lipid accumulation in a new model of non-alcoholic fatty liver disease

Abstract: BackgroundIn vitro exposure of liver cells to high concentrations of free fatty acids (FFA) results in fat overload which promotes inflammatory and fibrogenic response similar to those observed in patients with Non-Alcoholic Fatty Liver Disease (NAFLD) and Non-Alcoholic Steatohepatitis (NASH). Since the mechanisms of this event have not been fully characterized, we aimed to analyze the fibrogenic stimuli in a new in vitro model of NASH.MethodsHuH7 cells were cultured for 24 h in an enriched medium containing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 34 publications
11
110
0
1
Order By: Relevance
“…The present study used FFAs to establish a cell model of human NAFLD. The results showed triglyceride accumulation in HepG2 cells after treatment with FFAs, consistent with previous studies [27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study used FFAs to establish a cell model of human NAFLD. The results showed triglyceride accumulation in HepG2 cells after treatment with FFAs, consistent with previous studies [27][28][29][30].…”
Section: Discussionsupporting
confidence: 81%
“…Saturated palmitic (PA; C16:0) and monounsaturated oleic (OA; C18:1) acids are the most abundant FFAs in the liver triglycerides of patients with NAFLD [27,28]. Previous studies showed that in vitro NAFLD models induced by FFAs mixture (PA/OA, 1:2 ratio) could lead to triglyceride accumulation in hepatocytes similar to that of patients with NAFLD, with minor toxic and apoptotic effects [29,30]. The present study used FFAs to establish a cell model of human NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, phospo-IÎșBα and phospho-p65 levels were further enhanced by combined stimulation with both stimuli ( Figure 2D). Interleukin-8 (IL-8) and intercellular adhesion molecule 1 (ICAM-1) are two pro-inflammatory genes which are regulated by NFÎșB and which correlate with hepatic inflammation in ALD and NAFLD [26,27]. Notably, expression levels of IL-8 and ICAM-1 corresponded with phospo-IÎșBα and phospho-p65 levels in PHH stimulated with alcohol, oleate or their combination ( Figure 2E).…”
Section: Effects Of Alcohol and Oleate On Hepatocellular Lipid Peroximentioning
confidence: 95%
“…Friedman (Mount Sinai School of Medicine, New York, NY). Cells were grown in DMEM high glucose medium (ECB7501L-50, Euroclon, Italy) supplemented with 10% v/v (HuH7) (Chavez-Tapia et al, 2012) and 1% v/v (LX-2) (Xu et al, 2005) of fetal bovine serum (FBS) (ECS0180L, Euroclon, Italy), 2 mM L-Glutamine (ECB3000D, Euroclon, Italy) and 10,000 U/mL penicillin and 10 mg/mL streptomycine (ECB3001D, Euroclon, Italy). Simultaneous co-culture experiments were performed in 1% v/v FBS medium, in order to avoid LX-2 auto activation.…”
Section: Human Cell Lines and Culture Mediamentioning
confidence: 99%
“…Intracellular lipid droplets were determined by fluorescence microscopy based on Nile Red (N3013, Sigma Chemical USA) staining as described by Chavez-Tapia et al (2012). Briefly, cells were seeded in a coverslip and treated with FFA (1200 lM -24 h).…”
Section: Qualitative Analysis Of Intracellular Ffa -Nile Red Stainingmentioning
confidence: 99%